(untitled) - Shoukri, M. M. (Boca Raton, 2007)
New to the Third Edition : The introduction of R codes for almost all of the numerous examples solved with SAS; A chapter devoted to the modeling and analyzing of normally distributed variables under clustered sampling designs; A chapter on the analysis of correlated count data that focuses on over-dispersion; Expansion of the analysis of repeated measures and longitudinal data when the response variables are normally distributed; Sample size requirements relevant to the topic being discussed, such as when the data are correlated because the sampling units are physically clustered or because subjects are observed over time; Exercises at the end of each chapter to enhance the understanding of the material covered; An accompanying CD-ROM that contains all the data sets in the book along with the SAS and R codes
Keywords: Dịch tễ học,Epidemiology; Phương pháp thống kê,Statistical methods